Research on mechanical properties and impact resistance of origami-based metamaterial for GIL - Xu, Wei; Huang, Yinmao; Li, Haoran; Luo, Yan; Wu, Yang (Frontiers in Materials, 2023)
Gas insulated metal enclosed transmission line (GIL) is a high voltage, high current power transmission equipment, widely used in large hydropower stations, large-scale energy hubs and other occasions. Aiming at the shock environment that GIL may face, such as earthquake shock and water flow shock, a mirror folded mechanical metamaterial based on the Miura-ori patterned is proposed in this paper, and its mechanical responses and shock resistance performance were studied through the numerical simulation and experiment. The results showed that compared with the single-layer folded structure, the mirror connection mode increased the plastic hinge in the deformation process of the structure, causing the better energy absorption. Moreover, the parameters research indicated that reducing the plane angle and increasing the dihedral angle can improve the energy absorption. Most importantly, the structure can achieve more than 60% energy absorption under the impact load, showing a good buffer energy absorption effect. This paper can provide some significant reference and guidance for the impact resistance of the GIL in the practical engineering.